2019
DOI: 10.1002/hbm.24539
|View full text |Cite
|
Sign up to set email alerts
|

Resting state connectivity differences in eyes open versus eyes closed conditions

Abstract: Functional magnetic resonance imaging data are commonly collected during the resting state. Resting state functional magnetic resonance imaging (rs‐fMRI) is very practical and applicable for a wide range of study populations. Rs‐fMRI is usually collected in at least one of three different conditions/tasks, eyes closed (EC), eyes open (EO), or eyes fixated on an object (EO‐F). Several studies have shown that there are significant condition‐related differences in the acquired data. In this study, we compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 37 publications
15
104
0
Order By: Relevance
“…Incorporating novel methods for reducing in-scanner motion will be crucial in future studies to allow for longer scan times in developmental populations. In addition, past work has found that age-related differences in functional connectivity are only observable in resting state collected with eyes open or fixation, but not with eyes closed, as is the case in this study ( Agcaoglu et al, 2019 ). However, the fact that the resting state results were replicated in the PNC resting state data, which is collected with eyes open, likely mitigates this issue.…”
Section: Discussionsupporting
confidence: 50%
“…Incorporating novel methods for reducing in-scanner motion will be crucial in future studies to allow for longer scan times in developmental populations. In addition, past work has found that age-related differences in functional connectivity are only observable in resting state collected with eyes open or fixation, but not with eyes closed, as is the case in this study ( Agcaoglu et al, 2019 ). However, the fact that the resting state results were replicated in the PNC resting state data, which is collected with eyes open, likely mitigates this issue.…”
Section: Discussionsupporting
confidence: 50%
“…The entire scanning session lasted for 8 minutes. This procedure reflects recent evidence 70 showing that eyes open and fixated produce more reliable results for controlling experimental variability across participants.…”
Section: Computing Common and Specific Executive Function Componentsmentioning
confidence: 54%
“…Although the eyes-closed resting condition can lead to participants falling asleep during scanning and to more variability among responses ( Agcaoglu et al, 2019 , Patriat et al, 2013 , Tagliazucchi and Laufs, 2014 ), this choice was driven by methodological considerations. Firstly, DOC patients at the acute stage very rarely present with spontaneous eye-opening.…”
Section: Methodsmentioning
confidence: 99%
“…As detailed in the methodology section, we asked the participants to keep their eyes closed to mitigate, as much as possible, potential confounding effects associated with the clinical characteristics of the sample of patients, such as the inability of acute patients to keep their eyes open for 10 min. Nevertheless, we acknowledge that the eye-closed condition may lead some participants to fall asleep during the scanning session, causing a higher variability of the responses ( Agcaoglu et al, 2019 , Patriat et al, 2013 , Tagliazucchi and Laufs, 2014 ). To control for this risk, we interviewed healthy participants after each resting-state fMRI session about their state of wakefulness.…”
Section: Limitations Of the Studymentioning
confidence: 99%